Measuring intellectual capital efficiency in the Malaysian software sector - Kweh Q.L.; Chan Y.C.; Ting I.W.K. (2023)
Purpose: The purpose of this paper is to investigate the efficiency of Malaysian public-listed software companies in transforming intellectual capital (IC) into corporate values by using the data envelopment analysis (DEA) methodology. Design/methodology/approach: The authors use three individual components of value added intellectual coefficient (VAIC) as the input variables, and Tobin's Q and return on equity (ROE) as the output variables. Findings: Examining a sample of 25 companies, findings of this study show that companies listed on the main market of Bursa Malaysia are less efficient than those listed on the ACE market. Among the sample companies, Eduspec Holdings Berhad, which falls in the "stars" zone, is the most efficient company with the highest frequency of reference. The results remain robust despite the criticism about the validity of VAIC as an IC indicator. Practical implications: The benchmarking analysis of this study may shed light for the managers in software companies to benchmark and improve their efficiency in IC management. Originality/value: This is the first paper to examine the IC efficiency of Malaysian software companies through DEA. Emerald Group Publishing Limited.